Rules of engagement: reforms on its application and enforcement / Ahmad Shamil Abdul Hamid and Md Syazni Idris - Abdul Hamid, Ahmad Shamil; Idris, Md Syazni (2007)
The rules of engagement (ROE) are partly made to ensure civilian casualties and collateral damage is avoided. However, civilian casualties still occur, and at times, in alarming numbers or magnitude. This is due to the negligence of the parties of the military operation and most of the time blatant disregard of the ROE and indiscriminate engagement of both military and non-military targets. And because of that, a research on the ROE is necessary so as to determine its purpose, enforcement and its effectiveness. The research would study the flaws of the ROE and come into a conclusion as to the reasons why civilian lives are still being lost in armed conflicts to this day. Gaps in the laws or enforcement methods would be unearthed and through obtaining such information, the research would arrive at suggestions as to how to better the ROE, its enforcement and its effectiveness, and hopefully bring about a concrete protection for the innocent lives in a war. As to achieve this objective, the research would include a full analysis of the impact of the Vietnam War, namely the land occupation by US forces in the war, on these areas of international law. On the whole, it generally involved the application of established law to the events in question. Indeed the basic method adopted in this research is to attempt to give a clear description and, where necessary, clarification of the law governing armed conflict in international relations